Gender Disparities in Psychological Distress and Quality of Life: An In-depth Examination Among University Students - Jan, Afreen; Ahmad, Amir (International Journal of Psychosocial Rehabilitation, 2020)
The objective of this study was to investigate the association between psychological distress and quality of life in University of Kashmir students. The sample comprised 300 students (190 females and 110 males) enrolled across various departments. The instruments utilized for assessing Quality of Life and Psychological Distress were the WHO Quality of Life-BREF, 1991 (WHOQOL-BREF), and Kessler’s Psychological Distress Scale, 1992 (K10), respectively. The findings revealed a notable negative correlation between psychological distress and all dimensions of quality of life, including physical, social, environmental, and psychological aspects. Moreover, concerning gender, a significant difference was observed in the physical dimension, with male students scoring higher than female students, and in the environmental dimension, where females outscored males on Quality of Life.